2022
DOI: 10.3390/life12050673
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Cardiosplenic Axis in Patients with Fatal Myocardial Infarction

Abstract: Myocardial ischemia triggers neurohumoral activation of the cardiosplenic axis. In rodents, adverse outcomes occur upon prolonged entrance of mononuclear cells from the spleen into myocardial tissue. The purpose of this study is to assess the features of spleen structure in patients with fatal myocardial infarction (MI), the dynamics of macrophage infiltration of the spleen and its relationship with cardiac macrophage infiltration and unfavorable outcomes. Using immunohistochemistry techniques, we analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Ismahil et al then found that splenectomy post-MI reduces adverse cardiac remodeling, while the adoptive transfer of splenocytes from mice with ischemic heart failure is sufficient to produce adverse cardiac remodeling in naïve mice (16). Consistent with these findings, autopsies of patients with fatal MI revealed an accumulation of monocytes at the infarcted myocardium with concurrent monocyte depletion in the spleen (25,26). In another study of 22 patients with ischemic MI, fludeoxyglucose-18 (FDG) positron emission tomography (PET) revealed increased splenic inflammation post-MI relative to control patients (27).…”
Section: Discussionmentioning
confidence: 88%
“…Ismahil et al then found that splenectomy post-MI reduces adverse cardiac remodeling, while the adoptive transfer of splenocytes from mice with ischemic heart failure is sufficient to produce adverse cardiac remodeling in naïve mice (16). Consistent with these findings, autopsies of patients with fatal MI revealed an accumulation of monocytes at the infarcted myocardium with concurrent monocyte depletion in the spleen (25,26). In another study of 22 patients with ischemic MI, fludeoxyglucose-18 (FDG) positron emission tomography (PET) revealed increased splenic inflammation post-MI relative to control patients (27).…”
Section: Discussionmentioning
confidence: 88%
“…Однако возможно, что для лиц без ССЗ сниженный генез данного фенотипа клеток служит вариантом физиологической нормы, и, напротив, у лиц с ИМ недостаточный генез данного типа клеток с противовоспалительной активностью может обусловливать неблагоприятный исход, что подтверждают ранее полученные экспериментальные данные о полезной роли репаративных мф на ранней стадии воспаления и связи дефицита CD206+ в миокарде с фатальным исходом [12]. Низкое содержание данного фенотипа клеток при ИМ в КП наряду с их низким содержанием в БП может отражать истощение дан-ного типа клеток или их недостаточную выработку, что может обусловливать неблагоприятный исход [3,10]. Однако, согласно полученным ранее данным, не складывается однозначного впечатления о благоприятном или, напротив, негативном влиянии пониженного/повышенного содержания CD206+ клеток на процессы регенерации миокарда и клинические исходы в условиях острой ишемии миокарда [3,12,16].…”
Section: Discussionunclassified
“…ранее комплексное сопоставление количественного содержания спектра мф, включающих как мф М1, так и М2 типа, не проводилось ни в эксперименте, ни в клинике; не сравнивалось их содержание между лицами с ИМ и контрольной группой. Существующие ранее экспериментальные данные оценивали содержание либо одного из фенотипов мф в эксперименте [5], либо содержание предшественников мф -моноцитов [10].…”
Section: Discussionunclassified
“…The main clinical and anamnestic data of the study sample were reported in our studies into the morphometric characteristics of the spleen in patients with fatal MI [9]. The time from the onset of the disease to admission to the hospital was 180 min (120-720 min.).…”
Section: Clinical and Anamnestic Datamentioning
confidence: 99%